Survival strategies and stigma against the poor in the 1001 Malam community in Surabaya City - Teguh Imami (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
This study aimed to determine how the poor community in the 1001 Malam settlement, Surabaya, live their daily lives. Most settlers coming from villages and settling in cities (urbanization) are forced to become poor people who live under bridge tolls. Qualitative research was used to describe the lives of the settlers where the researchers interviewed 12 research subjects. This study employed the theory of symbolic interactionism proposed by George Herbert Mead, the theory of marginality proposed by Robert Park, and the theory of Stigma proposed by Erving Goffman. The results of this study indicate that settlers have a distinct sense of self and identity compared to residents of Surabaya City in general. Settlers define themselves as poor, uneducated, and without access to resources so they must work on the side to make ends meet. This study concludes that the settlers’ survival strategy is to work as buskers, beggars, scavengers, hawkers, and laborers. These informal jobs make poor communities stigmatized as criminals, poor, uneducated, and slum dwellers.